Exploring Labiodental Consonant Pronunciation Challenges Faced by Sundanese EFL Learners: Effective Strategies for Improvement - Fahrus Zaman Fadhly; Yuniarti Yuniarti; Fina Apriyani (Journal of English Language Teaching and Linguistics, 2022)
This study aims to explore the challenges faced by Sundanese EFL learners in pronouncing labiodental consonant sounds, specifically /f/ and /v/, and to propose effective strategies for improvement. The study focuses on collecting data from Sundanese EFL learners at various levels of proficiency using interviews and pronunciation tests. The results indicate that learners face various challenges in pronouncing labiodental consonants, such as substituting similar sounds from their native language and struggling with unfamiliar sound combinations. The study proposes several strategies to overcome these challenges, including drilling exercises, practicing with audio recordings, and promoting learner autonomy.